Assessment of knowledge, attitude, and practice on early childhood caries among dental undergraduates and residents in China - Jingjing Yu; Guangtai Song; Jian Yu (BMC Medical Education, 2024)
Abstract Background Early childhood caries (ECC) causes severe, widespread oral health issues in children. Dental undergraduates and residents are expected to have a solid understanding of ECC for children’s oral health promotion. This study aimed to evaluate the knowledge, attitude, and clinical practice on ECC among dental undergraduates and residents in China. Methods A 23-item electronic questionnaire was distributed to 598 dental undergraduates (4th- and 5th-year undergraduates) and residents (1st-, 2nd-, and 3rd-year residents) at the School of Stomatology, Wuhan University, China (in April–May 2023). SPSS Statistics was used to analyze the data using the Chi-square test at a significance level of 0.05. Results A total of 422 questionnaires were completed by participants (recovery rate: 70.6%) from various academic levels. Around 77.3% of participants had heard of ECC (mainly from textbooks), and only 27.5% considered themselves familiar with it. Residents (79.8%) had higher risk awareness of ECC on children’s overall health than undergraduates (58.3%) (p < 0.05), but only 54.0% of participants correctly defined ECC. Most participants had a positive understanding of ECC’s pathogenic factors and preventive measures, including feeding patterns (71.6%), fluoride application (93.4%), and teeth cleaning (93.1%). Furthermore, only 50.2% of participants encountered ECC cases in clinic. Conclusions Despite having a suboptimal level of ECC-related knowledge and practice, dental undergraduates and residents in China demonstrated a more positive attitude towards its etiology-based prevention. Strengthening ECC education, guidance, and practice may enable them to gain a better understanding of ECC learning, which would benefit children’s oral health.